2001
DOI: 10.1210/jcem.86.6.7536
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone (GH) Secretion in Patients with an Inactivating Defect of the GH-Releasing Hormone (GHRH) Receptor Is Pulsatile: Evidence for a Role for Non-GHRH Inputs into the Generation of GH Pulses

Abstract: GH secretion is regulated by the interaction of GHRH and somatostatin and is released in 10-20 pulses in each 24-h cycle. The exact roles in pulse generation played by somatostatin, GHRH, and the recently isolated GH-releasing peptide, Ghrelin, are not fully elucidated. To investigate the GHRH-mediated GH secretion in human, we investigated pulsatile, entropic, and 24-h rhythmic GH secretion in two young adults (male, 24 yr; female, 23 yr) from a Moroccan family with a novel inactivating defect of the GHRH rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(31 citation statements)
references
References 38 publications
3
26
0
2
Order By: Relevance
“…A small but significant GH response to GH secretagogues, compounds that are thought to stimulate GH secretion independently from the GHRHR, has been reported by others and us. 31,37 However, the response is very mild (possibly as a result of severe somatotroph hypoplasia) and is still consistent with the IGHD diagnosis.…”
Section: The Phenotypesupporting
confidence: 58%
“…A small but significant GH response to GH secretagogues, compounds that are thought to stimulate GH secretion independently from the GHRHR, has been reported by others and us. 31,37 However, the response is very mild (possibly as a result of severe somatotroph hypoplasia) and is still consistent with the IGHD diagnosis.…”
Section: The Phenotypesupporting
confidence: 58%
“…Passive immunization with somatostatin antiserum does not alter pulsatile GH release, but immunization with antibodies raised against both somatostatin and GHRH abolishes GH bursts [8]. In contrast to these findings, patients with an inactivating defect of the GHRH receptor gene maintain the regular frequency of the GH release with a diminished total 24-h GH production rate, suggesting that GH pulses are under the control of intermittent somatostatin withdrawal while the amplitude of GH pulses is driven by GHRH [9]. The fundamental role of somatostatin in the GH pulse generation has been supported by previous data describing that most of the descending phases of somatostatin pulses are associated with the initiation of GH pulses in goats [5].…”
Section: Introductionmentioning
confidence: 83%
“…Preceding studies revealed that patients with inactivating defect of the GHRH receptor gene still maintain the regular frequency of the GH release with a diminished total 24-h GH production rate [9]. Although these data seem to indicate that somatostatin, instead of GHRH, is responsible for the pulsatile release of GH, more studies are required due to the heterogenity and limited number of the patient pool used.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that somatostatin primarily modulates GH pulse timing in humans includes a rebound-like pulse of GH that occurs during short-term somatostatin withdrawal [40] and a reduction in the frequency and area of GH peaks but conserved GH pulsatility during intravenous somatostatin infusion [41]. The separate functions of GHRH and somatostatin for controlling GH pulse amplitude and frequency are uniquely demonstrated in young adults with a recessive point mutation that results in truncated and inactive GHRH receptors [42]. Compared with healthy adults, these individuals have extremely low serum GH concentrations because of very small GH burst amplitudes, but the GH secretory burst frequency is 2-to 3-fold greater than age-and sex-matched control subjects [42].…”
Section: Discussionmentioning
confidence: 99%
“…The separate functions of GHRH and somatostatin for controlling GH pulse amplitude and frequency are uniquely demonstrated in young adults with a recessive point mutation that results in truncated and inactive GHRH receptors [42]. Compared with healthy adults, these individuals have extremely low serum GH concentrations because of very small GH burst amplitudes, but the GH secretory burst frequency is 2-to 3-fold greater than age-and sex-matched control subjects [42].…”
Section: Discussionmentioning
confidence: 99%